Nanochannel array modified three-dimensional graphene electrode for sensitive electrochemical detection of 2,4,6-trichlorophenol and prochloraz - Zheng, Weiran; Su, Ruobing; Lin, Xingyu; Liu, Jiyang (Frontiers in Chemistry, 2022)
Rapid, convenient, and sensitive detection of pesticides and their metabolites in environmental or food samples is critical for assessing potential environmental and health risks. Here, a three-dimensional (3D) electrochemical sensing platform is proposed based on the integration of nanochannel array on pre-activated 3D graphene (p-3DG) electrodes with no need of additional adhesive layers, which enables rapid and sensitive detection of prochloraz and its metabolite 2,4,6-trichlorophenol (TCP) in environmental and food samples. Through two-step electrochemical polarization, organic phase anodic oxidation, and aqueous phase cathodic reduction, p-3DG electrodes with high active area and excellent electrocatalytic performance were obtained. Vertically-ordered mesoporous silica-nanochannel film (VMSF) can be rapidly grown on the surface of p-3DG by an electrochemical-assisted self-assembly (EASA) method. Taking advantage of the high electrocatalytic activity of p-3DG and the ability of nanochannels to enrich TCP through hydrogen bonding, the VMSF/p-3DG sensor can sensitively detect TCP in the range of 10 nM to 0.1 μM and 0.1 μM to 15 μM with a low limit of detection (LOD) of 2.4 nM. Compared with p-3DG and VMSF-modified 2D electrodes, the fabricated sensor has a wide detection linear range and low LOD. The coexistence of model interferents such as protein, surfactant, and humic acid did not affect the electrochemical response of TCP, confirming the high anti-fouling ability of the VMSF/p-3DG sensor. Rapid electrochemical detection of TCP in environmental water samples was achieved. In addition, prochloraz in vegetable and fruit samples was indirectly quantified by measuring its metabolite, TCP, which could be obtained by hydrolysis of prochloraz.